DETECTING AND PREVENTING OF PLAGIARISM IN THE STUDY PROCESS - Veikša, Ingrīda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The educational work is based on the acquisition and use of previously created cultural, artistic and scientific values for the purpose of student growth. In the educational process works created by other authors may be used without the author's consent and payment of remuneration, provided the necessary conditions are met. However, these works are not always used in good faith, and quite often students use them without references, thus assigning them to self-writing, or ordering them to be written by others, in violation of the principle of academic integrity. Creativity is the main criterion for creating an author's work. However, authors are often influenced by previous works of other authors that they have seen, heard, felt, which is quite natural. When this influence goes beyond originality, the newly created work is recognized as plagiarism, or appropriation of authorship.The aim of the study is to identify ways in which the works of other authors are unlawfully used in the study process, thus creating plagiarism, as well as offering solutions to reduce plagiarism.In the research was used an analytical method of scientific research and method of grammatical, teleological, systemical and historical interpretation of legal norms. For the conclusions were used inductive and deductive method of scientific research.In order to evaluate the legitimate use of the work of other authors in the study process, the data on recorded cases of plagiarism in universities in Latvia were reviewed. In order to analyse the issues of influence and misappropriation, disputes between authors of works in different countries were analysed.The results of research highlighted that Latvian legislation provides extensive and detailed rights for students, but does not impose any obligations to them, and this legal framework should be improved.